Smart mobile pet tracking system - Neoh, Howe Yik (2024)
Despite the significant advancements in IoT sector, many pet owners still rely on inefficient search methods such as physical searches, posters and social media advertising. These methods not only pose financial burdens in pet owners but are also time-consuming and offer no guarantee of successfully locating lost pets or ensuring their survival. Additionally, the emotional toll of losing a pet can be substantial to pet owners too. This smart mobile pet tracking system addresses these challenges by enabling pet owners to track their pets’ current locations and narrow down search areas based on their activity patterns. This project involves the development of a smart mobile pet tracking system designed for pet owners. The app allows pet owners to track their pets’ real-time location and view their pets’ travel path history which helps in determine their activity areas. The integration of a GPS tracking system ensures an unlimited tracking range.